171k views
2 votes
Square root of 5 + square root of 3 the whole divided by sqaure root of 5 - square root of 3

1 Answer

3 votes

Answer:

The answer is 4 + 15 .

Explanation:

You have to get rid of surds in the denorminator by multiplying it with the opposite sign :


( √(5) + √(3) )/( √(5) - √(3) )


= ( √(5) + √(3) )/( √(5) - √(3) ) * ( √(5) + √(3) )/( √(5) + √(3) )


= \frac{ {( √(5) + √(3) ) }^(2) }{( √(5) - √(3) )( √(5) + √(3)) }


= \frac{ {( √(5) )}^(2) + 2( √(5) )( √(3)) + {( √(3)) }^(2) }{ {( √(5)) }^(2) - { (√(3) )}^(2) }


= (5 + 2 √(15) + 3 )/(5 - 3)


= (8 + 2 √(15) )/(2)


= 4 + √(15)

User Arnekolja
by
5.4k points